Endodontic Management of Radix Paramolaris with Six Canals: A Clinical Case Report - Acharya, N; Singh, A; Samant, PS; Gautam, V (Kathmandu University Medical Journal, 2015)
Endodontic therapy of mandibular molars is a challenging task due to its varied root canal morphology. A mandibular first molar with additional buccal root (Radix paramolaris) and additional distolingual root (Radix Entomolaris) is an example of its varied anatomy. A successful management of atypical root canal configurations is an important aspect in determining the success rate of root canal therapy. The detail knowledge of the root morphology and canal anatomy allows the clinician for accurate location of the extra roots and canals and accordingly the refinement of the access cavity for the stress free entry of complex anatomy. Hence, for a successful root canal therapy, clinician must be aware of the external and internal anatomic variations .The aim of this clinical case report is to present and describe the unusual presence of two separate mesial roots and six root canals in mandibular first molar, detected during routine endodontic therapy. Kathmandu Univ Med J 2013; 11(4): 338-341